The Problem-Solving Decision-Making scale - translation and validation for the Portuguese language: A crosssectional study - Micaela Moura Gregorio (2020)
ABSTRACT Background: Since it is argued that the patient should have an active role in medical decision making but not all patients want the same degree of participation, it becomes important to be aware of the population's preferences in order to proceed accordingly. As far as we know, the preferred roles by the Portuguese patient population in medical decision-making have not been studied. Objectives: 1) To translate and validate the Problem-Solving Decision-Making scale into the Portuguese language. 2) To assess public preferences for roles of participation in treatment decision making in a representative sample of the Portuguese population. Design: Cross-sectional study. Methods: The Problem-Solving Decision-Making scale was translated from English to Portuguese and then back-translated to obtain a final version. The questionnaire was then applied from January to March 2019 during face-to-face interviews in a representative sample of the Portuguese population (n=301 people aged 20 years or more) to validate the Problem-Solving Decision-Making scale in a Portuguese population. At a later stage, we performed an analysis of the results obtained with the application of the questionnaire in a larger sample of 599 people to obtain their preferred roles in medical decision-making. Results: Principal component analysis was used to evaluate the validity of the internal structure of the scale. The results identified two components: problem-solving and decision-making with an explained variance of 65.9%. For internal consistency, three different techniques were used and applied to the two components. All of the items have very good internal consistency (problem-solving Cronbach's alpha=0.931 and decision-making Cronbach's alpha=0.951). Patients mostly want to give their doctor control over problem-solving tasks by giving scores closer to "Doctor alone", while in decision-making tasks the "Doctor and you equally" component is increased. Comparing the 3 vignettes, it is possible to see that the mortality vignette is the one where patients left the decision to the doctor the most, with the percentage of passive patients being 66.1%. In contrast, the quality of life vignette had a higher percentage of patients who wanted a shared role (44.3%) and was the only one in which there were people in the autonomous category (0.2%). In problem-solving component, preference's variations differences were statistically significant for age, area of residence, and educational level variables. In decision-making component, preference's variations differences were statistically significant for age, marital status, area of residence, health status, educational level, main occupation and profession variables. Conclusions: The validation of the Portuguese scale agreed well with the existing literature. The scale can be divided into two components: the problem-solving component and the decision-making component. The translated scale demonstrated good internal consistency and can therefore be used in future studies. In the Portuguese population, most patients leave to the physician the role of decision maker, both in the problem-solving and decision-making components. It is possible to observe the willingness to share the decision with the doctor in the decision-making but patients who want a completely autonomous role are rare. In a life-threatening situation, associated with a worse prognosis, patients are more willing to let the doctor decide. On the contrary, in a less serious situation there is a greater willingness to participate in decision making. We have found that shared decision making is more acceptable to younger and better-educated patients in problem-solving component and to younger, divorced, healthy, higher educated and employed, mostly who works on its own, people in decision-making component.